Acute Influenza B Infection Presenting as Cardiac Tamponade: A Case Report - Arfaras-Melainis, Angelos (Cureus, 2020)
Influenza A and B acute infections usually affect primarily the respiratory system. In rare cases, however, the cardiovascular system is also compromised either via the direct effect of the virus or via the worsening of preexisting cardiac conditions. We present a rare case of acute Influenza B infection presenting as pericardial effusion and cardiac tamponade. A healthy 32-year-old female was presented to the emergency room with influenza-like symptoms for four days, where she was monitored for a few hours and was subsequently discharged to home after testing positive for Influenza B by polymerase chain reaction (PCR). On the fifth day, she returned to the emergency room with worsening symptoms, primarily exertional dyspnea. She was hypotensive and tachycardic and temporarily improved with fluid administration. She was transferred to the intensive care unit, where a bedside point of care ultrasound (POCUS) and later a formal transthoracic echocardiogram revealed that she had pericardial effusion with sonographic signs of cardiac tamponade. Emergent pericardiocentesis was performed and resulted in hemodynamic and symptomatic improvement. The pericardial drain that was initially left in place and continued to drain pericardial fluid (700 ccs in total), was removed 3 days later, after echocardiographic confirmation of the resolution of the pericardial effusion. She completed a five-day course of Oseltamivir and was subsequently discharged home safely. In summary, our case describes an acute Influenza B infection that was complicated by pericardial effusion and cardiac tamponade. It also highlights the importance of bedside POCUS and echocardiography in the early diagnosis and treatment of cardiac tamponade cases, frequently with pericardiocentesis as in our case.